2013
DOI: 10.4041/kjod.2013.43.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone thickness and lower incisor position in skeletal Class I and Class II malocclusions assessed with cone-beam computed tomography

Abstract: ObjectiveTo evaluate lower incisor position and bony support between patients with Class II average- and high-angle malocclusions and compare with the patients presenting Class I malocclusions.MethodsCBCT records of 79 patients were divided into 2 groups according to sagittal jaw relationships: Class I and II. Each group was further divided into average- and high-angle subgroups. Six angular and 6 linear measurements were performed. Independent samples t-test, Kruskal-Wallis, and Dunn post-hoc tests were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 15 publications
4
40
1
6
Order By: Relevance
“…a mean of 1.2 mm difference). 18 The amount of alveolar bone thickness was significantly higher at the apical region as compared to the other two regions. These results were similar to the findings of Nauert et al and Nahm et al, who found gradual increase of bone thickness from the CEJ till the root apex level.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…a mean of 1.2 mm difference). 18 The amount of alveolar bone thickness was significantly higher at the apical region as compared to the other two regions. These results were similar to the findings of Nauert et al and Nahm et al, who found gradual increase of bone thickness from the CEJ till the root apex level.…”
mentioning
confidence: 86%
“…17 When Baysal et al compared alveolar bone thickness between skeletal class I and II malocclusions, the observations were that buccal alveolar bone thicknesses in class I patients were significantly greater than those in class II patients, and that the buccal apical alveolar bone thickness was greater than lingual in class II malocclusions. 18 Earlier studies about the density of the lower alveolar bone were made with the help of pyknometry, microradiography or histoquantification. 19 At present, bone density can be evaluated by different methods, as different tissue types absorb different amount of radiation.…”
Section: Jcdpmentioning
confidence: 99%
See 2 more Smart Citations
“…Joshi et al (2014) determinó diferencias morfológicas en situación espacial y morfología máxilo mandibular en sujetos con deformidades faciales, transformándolo en un elemento importante para definir condiciones de la morfología asociada. Baysal et al (2013) indicaron diferencias significativas entre sujetos clase I y clase II dentaria al comparar el tamaño sagital de la cortical ósea en tomografía computarizada; ellos confirmaron que los sujetos clase II presentan menor tamaño óseo de la cortical anterior en áreas próximas al diente. También, Sharma et al (2012), indicaron que el tamaño de la cortical ósea bucal seria asociada al modelo de crecimiento craneofacial, estableciendo relaciones entre el tipo de deformidad facial y las características del hueso cortical.…”
Section: Discussionunclassified